Individualized radiotherapy by combining high-end irradiation and magnetic resonance imaging Individualisierte Strahlentherapie durch Kombination von „High-end“-Bestrahlung und Magnetresonanzbildgebung - Combs, Stephanie E.; Nusslin, Fridtjof; Wilkens, Jan J. (Strahlentherapie und Onkologie, 2016)
Image-guided radiotherapy (IGRT) has been integrated into daily clinical routine and can today be considered the standard especially with high-dose radiotherapy. Currently imaging is based on MV- or kV-CT, which has clear limitations especially in soft-tissue contrast. Thus, combination of magnetic resonance (MR) imaging and high-end radiotherapy opens a new horizon. The intricate technical properties of MR imagers pose a challenge to technology when combined with radiation technology. Several solutions that are almost ready for routine clinical application have been developed. The clinical questions include dose-escalation strategies, monitoring of changes during treatment as well as imaging without additional radiation exposure during treatment.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Image-guided radiotherapy; Individualized medicine; Magnetic resonance-guided radiotherapy; Organ sparing treatments; Organs at risk